A study: cryptology techniques and methodologies - Safitri, Cutifa; Shoukat Ali, Haroon; Ibrahim, Jamaludin (International Journal of Science and Research, 2013)
Cryptography, as the most important aspect in the never ending evolving information technology era, is being criticized in its aspect. Information outbreaks make users doubtful on relying on their own information in current cryptosystems. This paper attempts to define the existing cryptology techniques and measures how strong and ‘bullet proof’ they are. In this paper, a basic encryption, byte to byte and complex encryption is shown as a study of cryptosystem classes that were used to overcome the need from various users. By understanding the current world phenomenon, it would be easier to answer the question of how secure cryptology actually is.